SOCIETY «FARMER» IN THE CAMP OF UKRAINIAN PRISONERS OF WAR WETZLAR (GERMANY), 1916-1917: TO THE HISTORY OF FOUNDATION AND ACTIVITY - SRIBNYAK, Ihor; PALIIENKO, Maryna (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2021)
The article recreates the history of creation and activity of the society «Farmer», which operated in the camp of Ukrainian prisoners of war Wetzlar (Germany) in 1916-1917, and identifies the contribution of its members to the cultural and educational life of the Ukrainian organization of the camp. Measures of the Union for the Liberation of Ukraine in the autumn of 1915 carried out the Ukrainization of the Wetzlar camp, after which it became possible to create a Ukrainian camp organization. The main content of her work was the establishment of cultural and educational life among the captive Ukrainians, which had a distinct national feature. In order to attract the apolitical part of Ukrainians to Ukrainians, the leadership of the camp community considered it expedient to establish the Farmer's Society, in which everyone had the opportunity to gain basic knowledge in the field of agronomic sciences beyond any «politics». To a large extent, the success of the society was ensured on the one hand by the attention paid to it by the members of the IED Education Department and the camp staff, and on the other hand, the German commandant's office provided significant assistance to the Farmer, handing over a separate barracks and a plot of land. In addition, the development of the society was facilitated by the Wetzlar Agricultural School (by borrowing visual aids and fertilizer samples). Due to this, the activities conducted by the society were practical and related to various fields of agricultural knowledge (horticulture, horticulture, animal husbandry, beekeeping, household chemicals, cooperation, etc.). The classes («seminars») involved not only professionals but also students from different regions of Ukraine, who prepared their own essays and introduced their colleagues to advanced management methods. It was also important that all lectures were given in Ukrainian, serving the cause of Ukrainization of some of the Russification prisoners. Gaining knowledge and receiving practical training, the members of the society at the same time diversified the diet of the rest of the camp, so the activities of the «Farmer» always met with general support of the entire camp community.